Pengaruh Good Governance, Pengelolaan Keuangan Daerah dan Sistem Pengendalian Intern Pemerintah pada Kinerja Pemerintah Daerah - Prasatyayang, Muhammad Rayindha; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 21 No 2 (2017)DO - 10.24843/EJA.2017.v21.i02.p18, 2017)
Local Government Performance is the performance of local government work achieved in realizing the targets set. The purpose of this study is to determine the effect Influence of Good Governance, Financial Management and Internal Control Systems Government (SPIP) on Local Government Performance. This study was conducted in 33 work units (SKPD) in the town of Bima and each SKPD taken four respondents, the agency heads and three heads of the subdivisions. The data used in this study are primary data obtained directly by distributing questionnaires to 132 respondents using purposive sampling technique. Data analysis techniques used in this research is multiple regression (Multiple Regression). The results of this study stated that Good Governacne, Financial Management and SPIP have a positive influence on Government Performance
Keywords: : Good Governance, Financial Management, Internal Control System of the Government, the Government Performance